Commentary on the Gospel of St John ; v.2 - Hengstenberg, Ernst Wilhelm, 1802-1869 (Minneapolis, MN Klock and Klock)
Contents : v. 1 : John XI. 1- XXI.25 ; concluding observations. Includes bibliographcial references.
Originally published by T. and T. Clark, Edinburgh, Scotland, 1865. This reprint : 1980
Keywords: Bible. N.T. John XI-XXI -- commentaries